PWE-054 Does Double Balloon Enteroscopy Have A Role In The Young with Iron Deficiency Anaemia? A Multicentre European Study. (17th August 2016) - Ching, H-L; Branchi, F; Yung, DE; Koulaouzidis, A; Plevris, J; Elli, L; Sanders, DS; Sidhu, R
Abstract : Introduction: Double balloon endoscopy (DBE) has been reported to have a high diagnostic yield in obscure overt gastrointestinal bleeding (OGB). There is paucity of studies of DBE for the indication of iron deficiency anaemia (IDA) alone particularly in the young. We investigated the utility of DBE in patients referred with IDA according to age. Methods: All consecutive patients undergoing DBE for IDA and OGB, between June 2006 and January 2016, across 3 teaching hospitals in the UK and Italy were included in the study. Demographic and clinical data were collected and patients were categorised by age (≥55 and <55 years) and those undergoing DBE for IDA or OGB. Diagnostic and therapeutic yields as well as complication rates were determined and compared. A secondary comparison was made between patients with IDA and overt bleeding in similar age groups. Results: 213 patients underwent DBE for IDA. 142 (66.7%) were age ≥ 55 years (mean age 69.6±8.6, 49.3% male) and 71 (33.3%) age <55 years (mean age 42.7±9.2, 66.2% male). The most common pathologies found at DBE (≥55 vs <55 years) were angioectasias (45.1% vs 18.3%, p < 0.05 ), tumours (4.9% vs 5.6%, p = 1), and ulcers (4.9% vs 8.5%, p = 0.37). Diagnostic yield was higher in those aged ≥55 years (≥55 vs <55 years; 64.1% vs 39.4%, p < 0.05 ). Therapeutic yield and complication rates on the other hand were comparable across both groups (30.3% vs 21.1%, p = 0.19 and 2.1% vs 4.2% p = 0.40 respectively). Further comparisons between young patients aged <55 years with IDA and those in the same age group with OGB (n = 23, mean age 43.5±8.8, 47.8% male) revealed similar frequencies of angioectasias (18.3% vs 13%, p = 0.75), tumours (5.6% vs 8.7%, p = 0.63) and ulcers (8.5% vs 0%, p = 0.33). There was no difference in the rate of positive capsule endoscopy findings preceding DBE between the two groups (59.2% vs 47.8%, p = 0.47). Diagnostic yield (39.4% vs 47.8%, p = 0.63) and therapeutic yield (21.1% vs 17.4%, p = 1) were also comparable while the difference in complication rates did not reach statistical significance (4.2% vs 0%, p = 1) between young IDA and OGB patients. Conclusion: We present the first multicentre study evidencing the safety and high diagnostic yield of DBE in patients with IDA. Although the diagnostic yield is lower in the young, significant pathology is detected including tumours and ulceration, supporting the role of DBE in young patients with IDA. Disclosure of Interest: None Declared